Dynamic light scattering system with a novel scattering cell for the measurement of particle diffusion coefficients - Will, Stefan; Leipertz, Alfred (Review of Scientific Instruments, 1996)
We present a novel optical scattering cell for the determination of the particle diffusion coefficient by dynamic light scattering, which can be utilized for particle size analysis and viscosity measurements. A major advantage of the light scattering setup introduced is the possibility of performing measurements without having to know the refractive index of the liquid used. Test results are given for the diffusion coefficient of silica particles in water, which show a total standard deviation including measurements at different angles of 0.5%. (C) 1996 American Institute of Physics.